2022
DOI: 10.3389/fpsyg.2022.920878
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Enhancing Phone Activeness on the Negative Effect Induced by the Presence of a Cell Phone

Abstract: In the information-driven workplace, cell phones have gradually become irreplaceable. Although the use of work-related cell phones can bring convenience, recent research has demonstrated that the presence of a cell phone can impair cognitive task performance by reducing available attentional resources and suggested that the effect of the phone’s presence can be influenced by phone-related factors. This study focused on the relationship between this effect and phone activeness and conducted two experiments to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Further, the individual's circumstances may be an important factor for predict their responses to cell phone removal [2]. If an individual is engaged in a task that requires signi cant attention, the removal of their cell phone might increase happiness because of improved focus and e ciency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the individual's circumstances may be an important factor for predict their responses to cell phone removal [2]. If an individual is engaged in a task that requires signi cant attention, the removal of their cell phone might increase happiness because of improved focus and e ciency.…”
Section: Discussionmentioning
confidence: 99%
“…In daily life, most people are constantly besieged by the distraction of checking their cell phone [1]. Studies have shown that the mere presence of a cell phone, regardless of whether it is on or the individual has physical contact with it, may serve as a distraction [2]. Given the prevalence of cell phone use, researchers have begun to investigate the impact of cell phone possession and removal on affect.…”
Section: Introductionmentioning
confidence: 99%
“…Smartphones had to be visually present in the smartphone presence condition. Upon further examination of the 786 potentially eligible records, 29 records (contributing 33 unique studies with 53 samples) met all inclusion criteria, 1 of which 19 were journal articles (Boila et al, 2020;Canale et al, 2019;Hartmann et al, 2020;Ito & Kawahara, 2017;Johannes et al, 2018Johannes et al, , 2019Kaminske et al, 2022;Koessmeier & Büttner, 2022;Linares & Sellier, 2021;Liu, Dempo, Kimura, et al, 2022;Liu, Dempo, & Shinohara, 2022;Nakagawa et al, 2022;Niu et al, 2022;Pellowe et al, 2015;Ruiz Pardo & Minda, 2022;Skowronek et al, 2023;Tanil & Yong, 2020;Thornton et al, 2014;, nine were unpublished theses or dissertations (Aguila, 2019;Bailey, 2018;Beijer, 2020;Bianchi Bosch, 2018;de Werd, 2020;Ruiz Pardo, 2022;Stahl, 2018;Stone, 2020;Tarantino, 2019), and one was a conference poster (Lyngs, 2017).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…All eligible records were made available from 2014 to 2023 across 12 countries (Australia, Canada, China, France, Germany, Italy, Japan, Malaysia, the Netherlands, Switzerland, the United Kingdom, the United States) in four continents (Australia, Asia, Europe, North America), with 30.30% of studies being conducted in the United States. It is noteworthy that 24 records employed a between-subject research design (Aguila, 2019;Bailey, 2018;Beijer, 2020, Boila et al, 2020Canale et al, 2019;de Werd, 2020;Hartmann et al, 2020;Ito & Kawahara, 2017;Johannes et al, 2018Johannes et al, , 2019Koessmeier & Büttner, 2022;Linares & Sellier, 2021;Lyngs, 2017;Niu et al, 2022;Pellowe et al, 2015;Ruiz Pardo, 2022;Ruiz Pardo & Minda, 2022;Skowronek et al, 2023;Stahl, 2018;Stone, 2020;Tanil & Yong, 2020;Tarantino, 2019;Thornton et al, 2014;, while only five records (Bianchi Bosch, 2018;Kaminske et al, 2022;Liu, Dempo, Kimura, et al, 2022;Liu, Dempo, & Shinohara, 2022;Nakagawa et al, 2022) employed a within-subject research design. The total sample size was 5,866 unique individuals (Mdn = 91, range = 25-520).…”
Section: Descriptives Of Eligible Recordsmentioning
confidence: 99%
“…People find themselves constantly distracted by the urge to check their cell phone [ 1 ]. Studies reveal that the mere presence of a cell phone can be distracting, regardless of its active use or physical interaction with the user [ 2 ]. Given the prevalence of cell phones, researchers are increasingly exploring how both the presence and absence of cell phones influence emotional well-being.…”
Section: Introductionmentioning
confidence: 99%